Unwrapping nutrition: Exploring the impact of hospital food and beverage packaging on plate waste/intake in older people. (1st January 2020) - Bell, Alison F.; Tapsell, Linda C.; Walton, Karen; Batterham, Marijka
Abstract: Food and beverage packaging is increasingly used in hospital food service provision. Previous research has identified that the packaging used in New South Wales hospitals can be difficult to open by older adults. As older adults experience high rates of malnutrition, it is important to understand the effects of packaging on actual consumption of food and fluids. The aim of this study was to explore the impact of hospital food and beverage packaging on dietary intakes of 62 independently living older people (65 years and over) in a university simulated hospital ward in NSW, Australia. Participants were allocated to either a breakfast and snack meal or a lunch and snack meal on two occasions one week apart. Meals were served in a shared ward environment and each participant experienced a 'sealed' and 'pre-opened' meal and snack condition. The nutritional status of participants was measured using the Mini Nutritional Assessment - Short Form (MNA®-SF) and intake was estimated through an aggregated plate waste method. Overall findings were not significant for dietary intakes and the 'sealed' versus 'pre-opened' conditions. However, for the seven participants classified by the MNA®-SF as 'at risk' of malnutrition, packaging impeded intake for breakfast (η 2  = −0.34) and the high protein snack (cheese and biscuits) (η 2  = −0.24) meals. This finding has implications for the provision of packaged high protein snacks (cheese portions) and breakfast meals for the older inpatient. Further research is required for nutritionally compromised and frail older people in the hospital environment to investigate the impact of packaging on food and beverage consumption in detail.